Upper atmosphere temperature structure at the Venusian terminators: A comparison of SOIR and VTGCM results. (August 2015) - Bougher, S.W.; Brecht, A.S.; Schulte, R.; Fischer, J.; Parkinson, C.D.; Mahieux, A.; Wilquet, V.; Vandaele, A.
Abstract: Venus Express SOIR terminator profiles of CO2 densities and corresponding temperatures have been determined for 132 selected orbits obtained between 2006 and 2013. These recently recalibrated measurements provide temperature profiles at the Venusian terminator over approximately 70–160 km, revealing a striking permanent temperature minimum (at about 125 km) and a weaker temperature maximum (over 100–110 km). In addition, topside temperatures (above 140 km) reveal a warming trend consistent with a typical thermospheric structure. These features are reflected in the corresponding CO2 density profiles, and provide detailed constraints for global circulation models of the upper atmosphere. New Venus Thermospheric General Circulation Model (VTGCM) simulations are presented for conditions appropriate to these SOIR measurements. In particular, solar minimum to moderate fluxes are specified and mean values of eddy diffusion and wave drag parameters are utilized. Recent upgrades to the VTGCM code now include more realistic lower boundary conditions at 70 km near cloud tops. Model temperature profiles are extracted from the terminators that correspond to five latitude bins presently used in the SOIR data analysis. Averaging of VTGCM temperature profiles in each of these bins (at each terminator) is conducted to match SOIR sampling. Comparisons of these SOIR and VTGCM temperature profiles are shown. Most notably, the observed temperature minimum near 125 km and the weaker temperature maximum over 100–110 km are generally reproduced by the VTGCM at the correct pressure/altitude levels. However, magnitudes of simulated and measured temperatures are somewhat different as a function of latitude. In addition, VTGCM evening terminator (ET) temperatures are simulated to be modestly warmer than corresponding morning terminator (MT) values, a result of stronger ET than MT zonal winds at/above about 130 km. The SOIR terminator temperatures thus far do not reveal this consistent trend, suggesting the VTGCM climate based winds may not precisely represent the averaged conditions during SOIR sampling. Overall, these data-model comparisons reveal that both radiative and dynamical processes are responsible for maintaining averaged temperatures and driving significant variations in terminator temperature profiles. Abstract : Highlights: The observed SOIR temperature structure at the Venus terminators is generally reproduced by the VTGCM numerical model above 110 km. The magnitudes of VTGCM and SOIR temperatures are somewhat different as a function of latitude, and match best at low latitudes. VTGCM evening terminator temperatures are simulated to be modestly warmer than morning values above 130 km, unlike SOIR measurements. Both radiative and dynamical processes are responsible for maintaining SOIR bin averaged terminator temperatures.